CHARACTERISTICS OF SCHOOL TEACHERS IN DIGITAL TRANSFORMATION SCENARIOS - Hutthayamad, Manot (Journal of Bovorn Multi-Education and Human Social Sciences ( JOB_EHS ), 2022)
This article presented the characteristics of school teachers in digital transformation situation, consisting of 1) 7 characteristics of good teachers, namely (1) lovely, (2) respectful, (3) pleasing, (4) able to speak effectively, (5) patience with words, (6) know how to teach something from easy to hard and (7) not be influenced in a way that was disgraceful, 2) a good teacher must have knowledge and ability according to concepts and theory in teaching and skills, being a good manager, having a professional ethics of teachers and happiness in both their own benefit and the benefit of others in their performance, being a good model for nation and a role model for students to be proud of their own teaching career with the spirit of being a national teacher and 3) 3 characteristics standards of teachers in the digital era: 1st standard was teachers must guide, help, inspire learning, 2nd standard was teachers must develop and design and 3rd standard was teachers must promote digital citizenship model.